Self Care Education Terhadap Kualitas Hidup Pasien Penyakit Paru Obstruktif Kronik (PPOK) - Nita Arisanti Yulanda; Ericha Rizki Ridhowati; Mita Mita; Anggelisa Larasati (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Chronic obstructive pulmonary disease (COPD) is a disease characterized by symptoms of persistent breathing and limited air flow, so COPD patients often experience symptoms of shortness of breath. Poor quality of life of COPD patients is characterized by symptoms of cough that are experienced every day, phlegm, tightness, limited daily activity at home, worry about leaving the house due to lung conditions, and disturbed sleep patterns. The purpose of this study is to analyze the effect of self-care education on the quality of life of COPD patients. The research design uses a pre-experimental design, with a one group pretest-posttest design approach. COPD patient population registered at UPT. West Kalimantan Lung Health Services. The sampling technique used purposive sampling with criteria: stable COPD patients who underwent outpatients, aged less than 60 years, patients who could read and write. Total sample of 30 patients. The independent variable of self-care education and the dependent variable is quality of life a measured by the SGRQ questionnaire (Saint George’s Respiratory Questionnaire). Before being given self-care education respondents will be pretested and continued giving self-care education to COPD patients for 4 weeks with education as much as 9 meetings then posttest. Data from the pretest-posttest were analyzed using the Paired t-test with value of p = 0,000 which means there were significant differences in the quality of life of COPD patients before and after the intervention. Nurses are expected to be able to provide education in improving the quality of life of COPD